Behavioral Changes In Elderly Hypertension In Covid-19 Prevention - Siti Badriah; Putri Mayang Sari; Lily Herlinah; Athanasia Budi Astuti (Poltekkes Kemenkes Surakarta, 2022)
Background: COVID-19 is a disease that can infect everyone, especially vulnerable groups such as the elderly with hypertension. Various educational institutions have carried out COVID-19 transmission, but they are still one-way and not very effective in suppressing COVID-19 spread. Therefore, in this study, health education will be conducted using the Focus Group Discussion (FGD) method so that this study aims to determine the effect of health education with the focus group discussion method on the behavior of the elderly with hypertension in preventing COVID-19. Methods: This study used a quasi-experimental design with 56 respondents for two groups (intervention group = 28 and control group = 28). Multistage cluster sampling was taking samples. The research instrument was a previously tested knowledge, attitude, and skills questionnaire for validity and reliability. The study was conducted at the Muara Enim Health Center. The data collected was processed using SPSS version 25.0 and analyzed by univariate (frequency and percentage) and bivariate (paired t-test and independent t-test). Results: The results of this study indicate an effect of health education using the FGD method on the behavior of the elderly with hypertension in preventing COVID-19 (p = 0.01). Conclusion: Health education with the FGD method can improve the behavior of the elderly with hypertension. For further research, it is necessary to involve the family as a support system in implementing health education with the FGD method using the Zoom application to increase the aggregate knowledge of the elderly in the community.